Changes of free fatty acids during ripening of Niva cheese - E. Vítová; J. Zemanová; Š. Bezděková; L. Babák; B. Loupancová; P. Březina (Czech Journal of Food Sciences, 2004)
Changes in the concentrations of free fatty acids in Niva cheese were monitored over the ripening period. Fatty acids were analyzed as methyl esters using gas chromatography with flame ionization detection. Identification has been carried out by comparison of the retention times with those of standard substances. Methanol esterification method using potassium hydroxide catalysis was used for preparing the sample of the fatty acids. The method is simple in respect to instrumentation and chemicals. It can be applied directly to the cheese matrix, which significantly decreases the time for sample preparation. There were total of 30 fatty acids identified in the cheese. Capric, myristic, palmitic, stearic and oleic acids represented the largest proportion of acid content and the most significant changes during ripening.